Electrical behaviors of (1-x)BZT07-xBNWT lead free solid solution binary system - Gobwute Rujijanagul (2018)
Solid solutions of the (1-x)Ba(Zr0.07Ti0.93)O3-xBa((Ni0.5W0.5)0.1Ti0.9)O3 system with 0.05 ≤ x ≤ 0.2, were fabricated via a solid-state reaction technique. All samples exhibited a pure phase perovskite structure. The x = 0.05 samples exhibited very high dielectric constants (>60,000) for temperatures over 400°C, while the x = 2.0 samples had a higher degree of dielectric constant stability over a wide temperature range. The ceramics also showed a dielectric relaxor behavior. The frequency dependence of the loss tangent peak was observed to follow an Arrhenius law where the activation energies increased with increasing Ba((Ni0.5W0.5)0.1Ti0.9)O3 content. The result suggests that the addition of Ba((Ni0.5W0.5)0.1Ti0.9)O3 has strong effects on the properties this ceramic system. © 2013 The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht.